The SCIENTOMETRIC ANALYSIS OF QUARTERLY JOURNAL OF INDIAN JOURNAL OF ANIMAL NUTRITION (IJAN) - L., Rajendran (International Journal of Research -GRANTHAALAYAH, 2021)
Using scientometric analysis, animal nutrition research from 2016 to 2020 was collected from the quarterly journal of the Indian Journals of Animal Nutrition. According to the research, 384 papers were written between 2016 and 2020, with 24 papers being highly published in 2016. As a result, animal nutrition is the most popular topic among scientists interested in veterinary research, with 1838 papers published out of 384. In particular, author Chander Data published 15 publications in the years (2016, 2017, 2018, and 2020), and some authors published (2,3,4,5,6,7,8,9,10,11,12) articles in the years (2016, 2017, 2018, and 2020).